Pemberdayaan keluarga yang Mempunyai Anggota Keluarga Menderita Gangguan Jiwa di UPTD Kesehatan Sukorejo Kota Blitar - Suprajitno Suprajitno; Yuni Tanzilla April Liani (STIKes Patria Husada Blitar, 2016)
Mental illness in Indonesia has a prevalence of 6% for ages 15 and over, or about 14 million people. In order to prevent the continued development of health problems related to mental disorders, family members need to be empowered and increased the ability which includes 5 basic tasks in the field of family health. The purpose of this research was to describe the empowerment of families who had a mental disorder member in UPTD Health Sukorejo. The research method used descriptive design. The population in this study was families who had mental disorder member in the District Sukorejo as many as 33 families, the sample was 30 families. The sampling technique used purposive sampling and the instrument used FES (Family Empowerment Scale) from Koren, et. all. Family empowerment said to be optimal if the average of 56.66. The results showed an average of 36.25 Â± 6.110 family empowerment means empowerment of the family had not been optimal. This was possible because most of the care for people with mental disorders was maternal age> 50 years, elementary education and did not work and care for people with mental disorders for> 10 years. The study was expected health workers could provide health services in cooperation with various related parties, socializing and management of mental disorders in the community could be optimized.